2018
DOI: 10.1039/c8ra08563c
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of DIO additive on charge extraction and recombination in organic–inorganic hybrid MAPbI3−xClx perovskite solar cell

Abstract: The additive of DIO not only can increase the PCE of perovskite solar cell, but also can decrease the bimolecular recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Thanks to all the aforementioned features, we anticipate that high-quality MAPbI 3– x Cl x perovskite films were successfully deposited from precursor solutions containing green α-terpineol alcohol as a solvent additive; PCEs as high as 17.5% were obtained for planar n–i–p PSCs, along with improved stability and reduced hysteresis. Considering that a very simple, low-cost one-step spin-coating technique was used (without the need of antisolvents), our results are very promising and competitive with those reported in the literature. ,, …”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Thanks to all the aforementioned features, we anticipate that high-quality MAPbI 3– x Cl x perovskite films were successfully deposited from precursor solutions containing green α-terpineol alcohol as a solvent additive; PCEs as high as 17.5% were obtained for planar n–i–p PSCs, along with improved stability and reduced hysteresis. Considering that a very simple, low-cost one-step spin-coating technique was used (without the need of antisolvents), our results are very promising and competitive with those reported in the literature. ,, …”
Section: Introductionsupporting
confidence: 51%
“…To circumvent this issue, a number of additive engineering strategies have been proposed, proving to be effective in enhancing the film quality and minimizing the recombination losses. The incorporation of additives into the photoactive layer is a method widely used also in the fabrication of organic solar cells (OSCs). In the context of PSCs, the mechanism behind this strategy is mostly related to the modulation of perovskite crystallization kinetics and to the passivation of defects and trap states. Various types of additives have been successfully applied, including fullerene derivatives, organic solvents, inorganic acids, , metal halide salts, ionic liquids, , organic small molecules, and polymers. Recently published works have demonstrated that interactions between organic solvents and perovskite components can be conveniently exploited to control the morphology and crystallinity of solution-processed perovskite films. Specific features such as a high-boiling point and/or strong Lewis base nature shown by commonly used solvent additives, including 1,8-diiodooctane, N -methyl-pyrrolidone, hexamethylphosphoramide, and dimethyl sulfoxide, have been found to be beneficial to promote the formation of uniform, highly crystalline perovskite films with larger grains. However, these solvents generally show high toxicity toward health and environment.…”
Section: Introductionmentioning
confidence: 99%
“…Then, to date, this additive strategy has been continuously applied for non-fullerene-acceptor (NFA)-based PSCs as well as all-polymer solar cells (all-PSCs) [ 59 , 66 ]. However, in the field of PeSCs, the conventional solvent additives such as DIO, CN, and ODT are relatively less studied for all-inorganic PeSCs although there are some for the hybrid PeSCs [ 67 , 68 , 69 , 70 , 71 ]. For example, in 2014, Jen and coworkers demonstrated that the bidentate halogenated additive, DIO can enhance the crystallization of MAPbCl 3 [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Chen and coworkers proved that the CN additive is beneficial to regulating the crystallization of MAPbI 3−x Cl x [ 68 ]. In 2018, Peng et al observed that the DIO additive also could enhance the crystallinity of MAPbI 3−x Cl x [ 69 ]. In the same year, Tsai et al proved that DIO is useful for the crystallinity, coverage, and uniformity of the MAPbI 3 thin film for PeSCs [ 70 ].…”
Section: Introductionmentioning
confidence: 99%